A response to a letter from David Perkins concerning the question of whether nt mutants involve tryptophan pyrrolase - F. A. Gaertner (Fungal Genetics Reports, 1981)
A response to a letter from David Perkins concerning the question of whether nt mutants involve tryptophan pyrrolase